Achieving sustainable development goals through adoption of hydrogen fuel cell vehicles in India: An empirical analysis. (8th February 2023) - Harichandan, Sidhartha; Kar, Sanjay Kumar; Bansal, Rohit; Mishra, Saroj Kumar
Abstract: Hydrogen is a growing facilitator for a multisectoral transition to a renewable energy-based economy. Despite this, there is negligible scholarly literature examining the connections between the hydrogen economy and the Sustainable Development Goals (SDGs) established by the United Nations. In this empirical investigation, we demonstrate a correlation between adopting Hydrogen fuel cell vehicles (HFCVs) and their direct and indirect impact on SDGs (#7, 9, 11, 12, 13, 14 and 15). This empirical investigation was performed based on 358 valid sample responses from the pan-India survey. Utilising structural equation modelling, the hypotheses were tested, and the research model was validated. The findings revealed that the adoption of HFCV has a positive impact on SDGs. The results confirm that policy implications significantly change public perception regarding high cost and infrastructure readiness. Keeping the finding in mind, we recommend that the fuel retailers create more hydrogen refuelling stations across the country to ease infrastructure bottlenecks. Further, governments at various levels should provide financial benefits to green hydrogen producers, fuel cell manufacturers, HFCV manufacturers, and early adopters of HFCVs in India. Graphical abstract: The above figure indicates the SDGs linked directly and indirectly to adoption of HFCVs. Image 1 Highlights: We examined public intention to adopt hydrogen fuel cell vehicles (HFCV). Adoption of HFCV significantly impacts (t = 5.4) Sustainable development goals (SDGs). Policy implications regarding HFCVs have a major impact (t = 8.6) on SDGs fulfilment. Risk perception and Safety concerns need to be addressed for better HFCV adoption.